Protective Effect Against Toxoplasmosis in BALB/c Mice Vaccinated With Recombinant Toxoplasma gondii MIF, CDPK3, and 14-3-3 Protein Cocktail Vaccine - Liu, Fang; Wu, Minmin; Wang, Jie; Wen, Hongyang; An, Ran; Cai, Haijian; Yu, Li; Shen, Jilong; Chen, Lijian; Du, Jian (Frontiers in Immunology, 2021)
Toxoplasma gondii can infect almost all endotherm organisms including humans and cause life-threatening toxoplasmosis in immunocompromised individuals, which leading serious public health problems. Developing an excellent vaccine is impending to against this disease. In present study, we formulated a cocktail protein vaccine including the TgMIF, TgCDPK3 and Tg14-3-3 proteins, which play critical roles in T. gondii infection. The recombinant proteins vaccines were constructed and assessed by vaccination in BALB/c mice. We organized the mice in various protein combinations groups of vaccines, and all mice were immunized with corresponding proteins at 0, 2, and 4 weeks. The specific protective effect of mice against T. gondii were analyzed by the mensuration of cytokines, serum antibodies, splenocyte proliferation assay, survival time and parasite cyst burden of mice after challenge. The study indicated that mice immunized with all three multicomponent proteins vaccine triggered a forceful immune response with highest levels of IFN-γ production and IgG antibody compared to other two proteins combinations and controls. Moreover, mild higher of IL-4 production and antigen-specific lymphocyte proliferation. The parasite cysts were significantly reduced (resulting in an 82.7% reduction) and survival time was longer in immunized mice with three multicomponent proteins compared with other groups mice. The enhanced humoral and cell-mediated immunity indicated that the protein cocktail vaccine containing three antigens provided effective protection for mice. These results indicated that recombinant TgMIF, TgCDPK3 and Tg14-3-3 multicomponent proteins were potential candidate for vaccine against toxoplasmosis.